2016
DOI: 10.1136/bmjsem-2015-000074
|View full text |Cite
|
Sign up to set email alerts
|

Does fair play reduce concussions? A prospective, comparative analysis of competitive youth hockey tournaments

Abstract: Background/aimTo determine if Boys Bantam and Peewee and Girls U14 sustain fewer concussions, head hits, ‘other injuries’ and penalties in hockey tournaments governed by intensified fair play (IFP) than non-intensified fair play (NIFP).MethodsA prospective comparison of IFP, a behaviour modification programme that promotes sportsmanship, versus control (non-intensified, NIFP) effects on numbers of diagnosed concussions, head hits without diagnosed concussion (HHWDC), ‘other injuries’, number of penalties and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
11
2
Order By: Relevance
“…Roberts et al 67 and Smith et al 68 demonstrated no difference in concussion risk with or without fair play rules in tournament play. However, Smith et al 68 demonstrated fewer non-injurious head contacts with ‘intensified’ fair play compared with ‘non-intensified’ fair play rules.…”
Section: Resultsmentioning
confidence: 98%
“…Roberts et al 67 and Smith et al 68 demonstrated no difference in concussion risk with or without fair play rules in tournament play. However, Smith et al 68 demonstrated fewer non-injurious head contacts with ‘intensified’ fair play compared with ‘non-intensified’ fair play rules.…”
Section: Resultsmentioning
confidence: 98%
“…Krolikowski et al 54 found that a policy of zero tolerance for head contact did not significantly reduce the risk of concussion in youth hockey. Smith et al 55 found that Fair Play systems, which incorporate sportsmanship and penalties into youth hockey game results, did not decrease the incidence of concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the actual policy related to concussions in professional football remains questioned and should be improved to protect the sustainable health of footballers. In ice hockey, the rule change related to eliminating checking to the head and banning hard plastic elbow pads has been proposed to prevent head injuries and protect players' health [34].…”
Section: Discussionmentioning
confidence: 99%